What is New about Globalization? The Multi-dimensional Impact of Globalization (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Globalization, as generally perceived, is not an economic phenomenon but has social, cultural and political dimensions too. Globalization has increased interdependence and competition between economies and world markets. It has led to emergence of worldwide production markets and greater access to range of foreign products. Newer financial products have allowed entrepreneurs companies to raise funds from external financial markets. The world has come much closer than it ever was. Politically it has led to creation of international level organizations which facilitate international relations and safeguard interests of smaller nations. Flow of information across the globe has increased through communication networks. English has emerged as the international language for communication.